1999
DOI: 10.3758/bf03199670
|View full text |Cite
|
Sign up to set email alerts
|

Intertrial interval effects in pavlovian serial feature positive discriminations

Abstract: The effects of the intertrial interval (lTI) on learning and performance in Pavlovian appetitive serial feature positive (SFP) discriminations were examined in three experiments with rats, Withlonger ITIs, acquisition was more rapid, and there was less transfer of the feature's behavioral control to a separately trained target cue, suggesting that longer ITIs encouraged the use of an occasion setting strategy. Behavior was also affected by discrimination-specific ITIs. Rats were trained with two SFP discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…Other studies have shown that the acquisition of Pavlovian conditioning may be improved with longer ITIs (Frey & Ross, 1968;Gibbon, Baldock, Locurto, Gold, & Terrace, 1977;Kehoe & Gormezano, 1974) and fewer trials per day (Kehoe & Gormezano, 1974). Similar benefits of trial spacing have been documented for the acquisition of serial feature-positive discriminations (Holland, 1995(Holland, , 1999. The possibility should not be discounted that a similar beneficial effect may occur for extinction and that, with parameters more similar to those used in the present experiments, Rescorla (1986a) and Holland (1989b) might have obtained a reduced enhancement effect.…”
Section: Discussionmentioning
confidence: 49%
“…Other studies have shown that the acquisition of Pavlovian conditioning may be improved with longer ITIs (Frey & Ross, 1968;Gibbon, Baldock, Locurto, Gold, & Terrace, 1977;Kehoe & Gormezano, 1974) and fewer trials per day (Kehoe & Gormezano, 1974). Similar benefits of trial spacing have been documented for the acquisition of serial feature-positive discriminations (Holland, 1995(Holland, , 1999. The possibility should not be discounted that a similar beneficial effect may occur for extinction and that, with parameters more similar to those used in the present experiments, Rescorla (1986a) and Holland (1989b) might have obtained a reduced enhancement effect.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies with this conditioning preparation also showed that 240-sec Is supported better learning than did shorter Is (e.g., Holland, 1995Holland, , 1999Holland & Morell, 1996), although those same studies showed that 480-sec Is supported either equivalent (Holland, 1995) or superior (Holland & Morell, 1996) learning. It is possible that the relation observed in Experiment 2 reflects a tradeoff between independent facilitatory effects oflonger Is and shorter Ts.…”
Section: Discussionmentioning
confidence: 86%
“…The present experiments do not distinguish between these two types of accounts. However, it is worth noting that Sunsay (2004) failed to confirm the comparator theory's prediction of an effect of extensive context exposure on performance to the CS when it was administered after conditioning when a short (240-sec) ITI had occurred (see also Holland, 1999). Finally, as we noted earlier, a time-accumulation model (Gallistel & Gibbon, 2000) would predict the role of context exposure only if it assumed that the internal clock that estimates reinforcement rate in the absence of the CS runs only in the context in which conditioning occurs.…”
Section: Note-this Article Was Accepted By the Previous Editorial Teammentioning
confidence: 99%